Status Stunting Dengan Prestasi Belajar Pada Siswa Sekolah Dasar Di Kecamatan Sukodono Kabupaten Sidoarjo Tahun 2012 - Asih Media Yuniarti; Hamam Hadi, MG. Adiyanti (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2014)
Background: The prevalence of stunting in children at District of Sidoarjo is 40.4%. In 2006 the prevalence was 23.5% and in 2010 was 29.4%. At Subdistrict of Sukodono the prevalence of stunting is 34.84%. Stunting is caused by chronic malnutrition that can lead to disorder in physical growth, brain development, optimum work capacity and health, as well as degree of concentration and intelligence which affect academic achievement. In a village at Subdistrict of Sukodono that has high prevalence of malnutrition, two of three elementary schools located in the village have the lowest result in score of National Test. High rate of stunting is feared to degrade academic achievement of elementary school children that affects quality of human resources.Objective: To assess association between stunting and academic achievement of elementary school students at Subdistrict of Sukodono District of Sidoarjo. Methods: The study was observational with cross sectional design. Location of the study was elementary schools at Subdistrict of Sukodono. The study was carried out by assessing height to identify stunting status associated with academic achievement in the subject of mathematics, Indonesian and natural sciences. Other factors observed were nutrition intake, eating pattern, education of parents, family income, number of family members, and role of parents as external variables associated with academic achievement. Results: There was statistically significant association (p=0.042 < 0.05) between stunting status and academic achievement. The result of multivariate test showed that stunting status, protein intake and duration of study statistically (p < 0.05) affected academic achievement. Conclusion: The majority of subject had normal status and most of stunting children had low academic achievement. Besides stunting status, protein intake and duration of study statistically affected academic achievement.